Paulo Orosio, Historias contra los paganos, Vol. i: Libr. i–iii, intr., ed., trad. y not., Fuentes de la Rosa, M. L., Madrid, Alma Mater, CSIC, 2022, 588 pp. ISBN: 978-84-00-11031-4 - Torres Prieto, Juana; Manzo, Elisa (Revista de Estudios Latinos, 2023)
Paulo Orosio, Historias contra los paganos, Vol.i: Libr.i–iii, intr., ed., trad. y not., Fuentes de la Rosa, M. L., Madrid, Alma Mater, CSIC, 2022, 588 pp. ISBN:978-84-00-11031-4